2015
DOI: 10.1371/journal.pone.0115541
|View full text |Cite
|
Sign up to set email alerts
|

Clinically Significant Fatigue: Prevalence and Associated Factors in an International Sample of Adults with Multiple Sclerosis Recruited via the Internet

Abstract: BackgroundFatigue contributes a significant burden of disease for people with multiple sclerosis (PwMS). Modifiable lifestyle factors have been recognized as having a role in a range of morbidity outcomes in PwMS. There is significant potential to prevent and treat fatigue in PwMS by addressing modifiable risk factors.ObjectivesTo explore the associations between clinically significant fatigue and demographic factors, clinical factors (health-related quality of life, disability and relapse rate) and modifiable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
108
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(120 citation statements)
references
References 64 publications
(69 reference statements)
10
108
1
1
Order By: Relevance
“…The study also showed a small inverse correlation between healthy diet and a 12-month relapse rate r = −0.117 with a 1.2% reduction in the 12-month relapse rate for each point increase in DHQ. This survey also separately evaluated fatigue in MS and its potential relationship with various dietary and physical health factors [10]. About two thirds of the survey participants reported clinically significant fatigue as assessed by the Fatigue Severity Scale (FSS).…”
Section: Introductionmentioning
confidence: 99%
“…The study also showed a small inverse correlation between healthy diet and a 12-month relapse rate r = −0.117 with a 1.2% reduction in the 12-month relapse rate for each point increase in DHQ. This survey also separately evaluated fatigue in MS and its potential relationship with various dietary and physical health factors [10]. About two thirds of the survey participants reported clinically significant fatigue as assessed by the Fatigue Severity Scale (FSS).…”
Section: Introductionmentioning
confidence: 99%
“…We have previously demonstrated modifiable lifestyle factors are important predictors in their own right of fatigue [32] and depression risk [33], and may therefore indirectly affect sexual function and satisfaction with sexual function. Here, we were able to demonstrate that diet and level of physical activity are associated with these outcomes even after adjusting for other relevant factors.…”
Section: Discussionmentioning
confidence: 99%
“…There is potential for a lifestyle risk factor modification approach to the management of SD in PwMS, given the strong associations of better lifestyle behaviours with reduced depression risk [33] and fatigue [32], both known to adversely affect sexual function [22]. In type 2 diabetes, another chronic disease with strong lifestyle associations, intensive lifestyle intervention in obese women resulted in a significantly greater proportion remaining sexually active, improvements in sexual function, and greater likelihood of remission of SD at 1 year [43].…”
Section: Discussionmentioning
confidence: 99%
“…Adopting healthy behaviours may be indirectly associated with QOL, as an externally oriented locus of control, with a feeling of being unable to influence health outcomes, predicts worse disability but also depression and fatigue [42], both determinants of QOL in their own right, and both strongly associated with the lifestyle factors examined here [43, 44]. Having healthy behaviours may be associated with positive orientation of locus of control, with attendant benefits in motivation to access health information and better adherence to treatment [42].…”
Section: Discussionmentioning
confidence: 99%